2014
DOI: 10.1002/2014jc010185
|View full text |Cite
|
Sign up to set email alerts
|

Formation and distribution of sea ice in the Gulf of St. Lawrence: A process‐oriented study using a coupled ocean‐ice model

Abstract: A coupled ocean-ice model for the eastern Canadian shelf is used to examine main physical processes affecting sea ice conditions in the Gulf of St. Lawrence (GSL) and adjacent waters. The coupled model is based on NEMO and uses OPA9 as the ocean circulation component and LIM2 as the ice model. The coupled model is forced by atmospheric reanalysis fields produced by Large and Yeager (2004). The model results are used to examine the roles of thermodynamics and dynamics on sea ice distributions and patterns of ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…While these parameters adopt constant values in the model, it is known that they can have strong temporal and spatial variability, for instance, in response to snow density and snow metamorphism (Meinander et al, 2013;Sturm et al, 1997). Other studies have also identified that the stability of the atmospheric boundary layer could affect clouds and sea ice, through modulations of the turbulent exchanges of heat and water vapor (Kay et al, 2016;Urrego-Blanco & Sheng, 2014). In EHV0, the air-ocean turbulent exchanges are estimated using Monin-Obukhov similarity theory, in which vertical gradients of momentum, temperature, and humidity are functions of coefficients C s and C u for stable and unstable atmosphere conditions, respectively, as defined by Large and Pond (1982).…”
Section: Experimental Design and Sensitivity Measuresmentioning
confidence: 99%
“…While these parameters adopt constant values in the model, it is known that they can have strong temporal and spatial variability, for instance, in response to snow density and snow metamorphism (Meinander et al, 2013;Sturm et al, 1997). Other studies have also identified that the stability of the atmospheric boundary layer could affect clouds and sea ice, through modulations of the turbulent exchanges of heat and water vapor (Kay et al, 2016;Urrego-Blanco & Sheng, 2014). In EHV0, the air-ocean turbulent exchanges are estimated using Monin-Obukhov similarity theory, in which vertical gradients of momentum, temperature, and humidity are functions of coefficients C s and C u for stable and unstable atmosphere conditions, respectively, as defined by Large and Pond (1982).…”
Section: Experimental Design and Sensitivity Measuresmentioning
confidence: 99%
“…Flow to the Gulf of St. Lawrence increases in warm months with snow melt. Sea ice forms in the Gulf in December and begins to spread seaward (east), eventually covering most of the Gulf, reaching its maximum extent in March, thereafter beginning to melt (Urrego‐Blanco & Sheng, 2014). The lack of distinctive areas of moderate to high correlation in the Gulf of St. Lawrence from the spatiotemporal analysis are likely due to a lack of data due to cloud cover and masking or inaccurate estimates of chl‐ a due to ice cover (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of distinctive areas of moderate to high correlation in the Gulf of St. Lawrence from the spatiotemporal analysis are likely due to a lack of data due to cloud cover and masking or inaccurate estimates of chl‐ a due to ice cover (Fig. 5A) (Urrego‐Blanco & Sheng, 2014). The Gulf of St. Lawrence is known to be highly productive, but higher productivity in the eastern region, has previously been attributed to upwelling (Savenkoff et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…All charts are then gridded on a 0.01°latitude by 0.015°longitude grid (approximately 1 km resolution). Following Table 3.1 of the Canadian Ice Service (2005) documentation, thickness (and therefore volume) is estimated from the mean thickness of stages of ice growth whether it is new ice (stage 1, <10 cm: 5 cm), nilas (stage 2, <10 cm): 5 cm), gray ice (stage 4, 10-15 cm: 12.5 cm), gray-white ice (stage 5, 15-30 cm: 22.5 cm), thin first-year ice (stage 7, 30-70 cm: 50 cm), medium first-year ice (stage 1•, 70-120 cm: 95 cm) and thick first-year ice (stage 4•, >120 cm: 160 cm), following a practice used by Peterson and Prinsenberg (1990) and Prinsenberg et al (1997) and routinely used for the validation of sea ice volume production in numerical models of the Gulf of St. Lawrence (Brickman & Drozdowski, 2012;Brickman et al, 2016;Saucier et al, 2003;Smith et al, 2013;Tang et al, 2008;Urrego-Blanco & Sheng, 2014). Prior to 1983, the CIS reported ice categories into fewer classifications using a single category of first-year ice (≥30 cm) with a suggested average thickness of 65 cm.…”
Section: Methodsmentioning
confidence: 99%